EFEKTIVITAS NCB (NATIONAL CENTRAL BUREAU) INTERPOL DALAM MENANGGULANGI PERDAGANGAN MANUSIA DI INDONESIA TAHUN 2012-2015 - Baihaqy, Ahmad; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The purpose of this research is to explain the effectiveness of NCB Interpol Indonesia in overcoming human trafficking in Indonesia in 2012-2015. National Central Bureau (NCB) is owned by every member of Interpol. The objective of its Formation itself is to overcome transnational crimes, including human trafficking. There are 47 human trafficking cases addressed by NCB Interpol Indonesia between 2012-2015.This research uses a neo-realism perspective which emphasizes that the state is the main actor and recognizes that non-state actors such as Intergovernmental Organizations (IGOs) have a role in international relations. This research is using the theory of the effectiveness of International Organizations by Frank Biermann and Steffen Bauer. NCB Interpol Indonesia is within the structure of the Indonesian National Police. this is in accordance with the assumption that the position of non-state actors is still under the authority of the state. Indonesia uses NCB Interpol Indonesia as the national bureau to tackle human trafficking in Indonesia.The results showed that NCB Interpol Indonesia was not effective in structural variable. The points that indicate the ineffectiveness of this international organization are unable to meet the points of formal competence, the level of regime that the regime does not possess, the overly complex organizational structure, the lack of personnel quantity in human resources of NCB Interpol Indonesia and not particularly the problem concern. In addition to other factors, ineffectiveness is also caused by poverty, low education and also ecological factor.Keywords: NCB Interpol Indonesia, Human Trafficking, Effectiveness